FILSAFAT PERAN TUKANG SANGIANG PEREMPUAN TERHADAP PENGARUSUTAMAAN GENDER KALIMANTAN TENGAH - Kunti Ayu Vedanti; Kinewati Kinewati; Rita Rita (Widya Katambung, 2025)
Marginalization and discrimination against women still occur and are inversely proportional to the need for inclusive gender participation in Indonesia's development. These problems and challenges require the elaboration of ideas, ideas and synergies of various parties to support gender mainstreaming. To meet these needs, research on the philosophy of women's sangiang is carried out with a qualitative descriptive method with literature research to find values that can be adopted to increase the motivation of empowered women. The value is that female sangiang role is represent the Hindu teachings that women have the opportunity to have a free profession according to their competence, of course they also have the same rights and obligations as men in development.